Econometric analysis of regional grain production in Ukraine - Vasylieva, Natalia; Васильєва, Наталя Костянтинівна (Іnternational Science Group, 2020)
Ukraine is the topic producer and exporter of cereals. The quantitative analysis of the regional growing was performed for Dnipropetrovsk region. Dynamics and stability of harvests and sown areas under wheat, barley and maize were compared with the national trends. The found reserves to increase the regional grain productivity were associated with scale of cereals production in agricultural enterprises, updating machinery and raising fertilizers applications under cereal crops. Дніпропетровській області. Розглянуто динаміку та стійкість валових обсягів, площ збирання й урожайностей пшениці, ячменю та кукурудзи на зерно і регіональні зміни у спеціалізації на їх вирощуванні відносно національних тенденції. Обґрунтовано резерви підвищення продуктивності у зерновій підгалузі регіону за рахунок масштабу виробництва сільськогосподарських підприємств, шляхом модернізації машинно-тракторного парку та збільшення внесення добрив під посіви зернових.
Економетричний аналіз регіонального виробництва зерна в Україні
Keywords: regional grain production; регіональне зерновиробництво; econometric models; економетричні моделі; trend; тренд; variation; варіація